2015
DOI: 10.1055/s-0035-1560506
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid or Lewis Acid Catalyzed [3+3] Cycloaddition of Azomethine Imines with N-Benzyl Azomethine Ylide: A Facile Access to Bicyclic N-Heterocycles

Abstract: Contents General Information S1 Preparation of N-Benzyl Substituted Compound 1 S1 General Procedure for the Synthesis of Azomethine Imines 3 S2 General Procedure for the [3 + 3] Annulation Reaction of N-Benzyl Azomethine Ylide 1 and Azomethine Imines 3 S2 Procedure for four-component one-pot Reaction of the [3 + 3] Annulation Reaction of N-benzyl-1-(trimethylsilyl)methanamine 5 and Azomethine Imines 3a. S2 Characterization Data for [3 + 3] Annulation Products 4 S3-S11 1 H and 13 C NMR Spectra of [3 + 3] Annula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…It has been reported that the S atom easily coordinates with the Cu ( Scheme 5 ) [ 28 , 29 , 30 ]. The coordination of DMSO with intermediate A resulted in the formation of intermediate B ([ B − I] + , m/z = 332.0387, please see Supplementary Materials Figure S4 ) [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the S atom easily coordinates with the Cu ( Scheme 5 ) [ 28 , 29 , 30 ]. The coordination of DMSO with intermediate A resulted in the formation of intermediate B ([ B − I] + , m/z = 332.0387, please see Supplementary Materials Figure S4 ) [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of 1,2,4-hexahydrotriazine derivative (36) was developed by Chao-Ze Zhu et alvia [Rh(NBD) 2 ]BF 4 catalyzed [3 + 3] cycloaddition reaction of (R)-vinyl aziridines (34) with Nimino isoquinolium ylide (35) (Scheme 12). [23] The product was formed through consecutive (б + п) rhodium species subse- [3 + 3]-cycloaddition reaction of α-acidic isocyanide with azomethine imine in presence of Cu catalyst.…”
Section: Metal Catalyzed Approachmentioning
confidence: 99%
“…An effective synthesis of fused six member triazine derivatives (62) was proposed by Shuoning-Li et al using the Brønsted acid or Lewis acid as catalyst via [3 + 3] cycloaddition of azomethine imine (2) with azomethine ylide (61) (Scheme 22). [34] The reaction was monitored with varying catalysts [TFA,TfOH,AcOH,HCl,HSbF 6 ,LiF,TBAF,TMSOTf,Zn (OAc) 2 , AgOAc, Zn(OTf) 2 , AgOTf, ZnCl 2 and TiCl 4 ], solvents (DCM, CHCl 3 , DCE, MeCN, DMF and THF) and reaction temperature (0, 10, 25 and 40°C). The highest yield was achieved when TFA was used as catalyst in DCM solvent at 10°C.…”
Section: Lewis Acid Catalyzed Pathwaymentioning
confidence: 99%
“…dropyrazolo[1,2-a][1,2,4]triazine derivatives 98 in good yields, however, no conversion was observed with the cyclohexyl-substituted dipole 47 (Scheme 30). 73 Finally, an interesting and unexpected formal [3+3] cycloaddition also took place upon treatment of dipoles 47 with N-vinylpyrroles 99 in the presence of silver trifluoroacetate in chlorobenzene at 120 °C. In the absence of a Lewis acid catalyst normal [3+2] cycloaddition took place (Scheme 30).…”
Section: Syn Thesismentioning
confidence: 99%